Penggunaan Ayat-ayat Syifa’ pada Ruqyah Tolak Sihir : (Studi Kasus pada Ustadz Muhammad Chudlori di Desa Watesari Kecamatan Balongbendo Kabupaten Sidoarjo) - Arini Jauharoh (Ushuluddin Faculty, PTIQ Institute, 2022)
This article is a living Qur'an research on the phenomenon of the practice of using Al-Qur'an verses as a repellent for magic. The case is understood from a phenomenological perspective (based on existing phenomena) which is implemented from an understanding of the verses of the Qur'an. The practice of using these verses of the Qur'an as a treatment for patients affected by witchcraft or known as ngeruqyah. This study uses a qualitative approach, and as an analytical theory, the author uses Max Weber's theory of social action. Researchers directly studied the situation in the field by observing and interviewing several informants. This research concludes that an activity carried out communally or individually is classified as a type of rational instrumental action with several goals and has a subjective meaning to be spread to other parties involved in social activities. The purpose of me-ruqyah on sick people caused by magic is as a representation of the Qur'an, non-medical treatment, and can calm the hearts of ruqyah patients. In addition, ruqyah is also understood and used as a medium of preaching for patients who come, both those who are still in the process of ruqyah and those who have recovered.